UV-Spectrophotometric Method for Citicoline: Development and Validation - Kiran Singh,; Meenu Bhatt,; Nidhi Sharma,; Prabhjot Singh,; Surbhi Bhatt,; Naveen Kumar, (The Bioscan, 2025)
A UV-spectrophotometric technique that is simple, sensitive, specific, rigid, precise, and repeatable was created and verified for the measurement of citicoline in tablet dosage form as well as in its pure form. The highest absorbance of citicoline in 0.1N HCl was observed at 280 nm. Between 10 and 80 μg/mL, the method showed linearity with a linear regression equation of Abs = 0.0111 x Conc and a correlation coefficient of 0.9999. The method's average accuracy was 98.41 ± 0.70%, and its precision was good (%RSD ~2%). It was shown that common excipients did not significantly interfere.